PENGARUH KARAKTERISTIK TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN EMISI KARBON - Missy Herlina; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
Awareness of many parties to global warming and climate change results in high demand for corporate responsibility for the environment. One form of corporate responsibility for the environment is the disclosure of carbon emissions. However, there are still few companies in Indonesia that disclose their carbon emissions. The disclosure of carbon emissions in this study focuses on the Carbon Disclosure Index (CDI) and Respond to the CDP (RCDP). This study aims to analyze whether the characteristics of corporate governance have an influence on the disclosure of carbon emissions by the company. The characteristics of corporate governance include the size of the board of commissioners, independent board of commissioners, gender diversity of the board of commissioners, and the diversity of the board of commissioners' nationalities.The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2013-2017. The selection of samples in this study used a purposive sampling method to obtain 41 companies with a total observation of 189 companies. Multiple linear regression analysis and logistic regression were used to test the hypotheses in this study.This research has only found that companies with increasingly large board size tend to respond to CDP. However, it was also found a negative relationship between independent commissioners and company decisions in response to CDP. In addition, this study did not succeed in finding a relationship between other corporate governance characteristics and disclosure of carbon emissions.